ANALISIS PELAYANAN ANGKUTAN UMUM PEDESAAN STUDI KASUS TRAYEK BALINGKA – AUR KUNING - Yoga Ferdian; Ishak Ishak; Zuheldi Zuheldi (Progressive : Journal of Advanced Engineering and Technology, 2026)
Balingka-Aur Kuning route public transportation is the only mass transportation in Balingka. Therefore, the quality of transportation services needs to be considered. The problem faced in an effort to improve public transportation services, namely capacity, schedule uncertainty, use of transportation exceeding capacity, road damage, and lack of consumer interest. capacity, road damage, and lack of consumer interest due to technological developments in transportation. technology in the field of transportation. Lack of consumer interest means a decrease in the number of passengers using public transport, which affects the operator's revenue and increases operational costs. operator's income and increasing operational costs. For this reason, a questionnaire was collected to determine passenger satisfaction with the performance of the Balingka public transport route Balingka - Aur Kuning, as well as to provide information and input to relevant agencies to further optimize their transportation fleet. Analysis results analysis showed that most respondents were satisfied with the physical condition of the facilities provided and were satisfied with the reliability of the facilities provided. facilities provided and are satisfied with the reliability and responsiveness of the service. Test The reliability test shows that the research questionnaire is reliable. However, there are some issues that need to be addressed, such as the limited number of fleets compared to the expected service standards. expected service standards. Although passenger loading is considered good enough, but a lower fleet size may affect service quality. The demographics of public transport consumers show that the majority of users are aged 21-30 years old.Keywords: Transportation, Questionnaire, Satisfaction, Limited